Evaluating the Incidence of Seizures and Its Relationship With Blood Glucose Levels in Tramadol Poisoning Patients Admitted to Imam Reza Hospital in Mashhad (Iran) From 2019 to 2020 - Seyed Reza Mousavi; Faezeh Jafari; Anahita Alizade Ghamsari; Mina AkbariRad; Majid Khadem-Rezaiyan; Seyed Amirhossein Mousavi; Sadaf Sadat Rafati (Journal of Toxicology)
Conclusion: Seizures in tramadol poisoning may be related to the patient’s blood glucose levels.